Germline-Restricted Chromosome (GRC) in Female and Male Meiosis of the Great Tit (Parus major, Linnaeus, 1758) - Torgasheva, Anna; Malinovskaya, Lyubov; Zadesenets, Kira; Shnaider, Elena; Rubtsov, Nikolai; Borodin, Pavel (Frontiers in Genetics, 2021)
All songbirds studied so far have germline restricted chromosome (GRC), which is present in the germ cells and absent in the somatic cells. It shows a wide variation in size, morphology and genetic content between the songbird species. In this paper, we analyzed GRC behavior in female and male meiosis of the great tit, using immunolocalization of SYCP3, the main protein of the lateral elements of the synaptonemal complex; MLH1, the mismatch repair protein marking mature recombination nodules; centromere proteins and trimethylated histone H3 at lysine 9, marking heterochromatic GRC in male germ cells. To estimate a homology of the great tit GRC with the sequences of its own basic chromosome set and GRCs of other species we carried out reverse and cross-species FISH with GRC-derived DNA probes of the great tit, zebra finch and pale martin. We found that despite dozens of million years of independent evolution the great tit GRC displays a striking similarity with the GRCs of two species of martins and two species of estrildid finches examined earlier. It was usually present in two copies in females forming recombining bivalent in pachytene cells and in one copy in males forming a condensed heterochromatic body with dotted-like axial elements of the synaptonemal complex. We observed mosaicism for the GRC copy number in both female and male great tit. This indicates that one of the GRC copies might be passively lost during premeiotic germ cell divisions. After meiotic prophase, the GRC was ejected from most male germ cells. However, we observed few spermatozoa containing GRC. This indicate that great tit GRC might be rarely transmitted to the progeny via the males. The reverse and interspecies FISH with GRC-specific microdissected DNA probes indicates that GRCs of the great tit, pale martin and zebra finch differ substantially in their genetic content despite similarities in the meiotic behavior.